Evidence-based teaching in nursing : a foundation for educators - Cannon, Sharon , 1940-; Boswell, Carol , 1945- (Sudbury, Massachusetts : Jones & Bartlett Learning, 2012)
"Designed to assist aspiring, novice, and experienced faculty members in obtaining a strong foundation for evidence-based teaching (EBT). Evidence-Based Teaching in Nursing: A Foundation for Educators explores past, present, and future aspects for teaching nursing in a variety of settings. This text promotes and demonstrates practical approaches for classroom, clinical, and simulation learning experiences while incorporating technology, generational considerations, and evidence. What's more, it addresses the academic environment while considering a wide array of teaching and learning aspects."